Ontogenesis of anselmian speculative thought - Corti, Enrique Camilo (Anales del Seminario de Historia de la Filosofía, 2019)
De concordia, the last treaty written by Anselmo constitutes a privileged high point in the ontogenetic process of his thought. I will try to outline the overall structural aspects of this text that I consider important to define its belonging to this ontogenic process: a) This work is inscribed —together with Monologio and Cur deus homo— in the process of construction of the anselmian speculative thought; b) The spectulative aspect is closely associated to language through the «nihil» notion; c) The articulation between freedom and necessity in M, and the unfolding of the centre of DC (in the textual centre and the objective centre) are both subsidiary to said aspect.